Retro-rectal leiomyoma About a case - Misa, Ricardo; Arévalo, Carlitos; Pirotto, Jorge (Cirugía del Uruguay, 2006)
The presacral or retrorectal tumors are particular/ y rare in the adult. They are tumors with variable histology, beca use it is a join zone in fetus from nervous and skeleta/ system and postana/ gut. The authors by means of a case report examine the patho/ogy, and the clínica/ and therapeutic approach. The tumor size, the pathologica/ type, the sacra! re/ation and special/y the anatomic situation with the Waldeyer fascia, are the principal elements for the choice of surgical transabdomina/ or sacra/ approach.